Interdomain Identity-Based Key Agreement Schemes. (30th November 2014) - Fan, Chun-I; Lin, Yi-Hui; Hsu, Tuan-Hung; Hsu, Ruei-Hau
Abstract : In order to simplify key management, two-party and three-party key agreement schemes based on user identities have been proposed recently. Multiparty (including more than three parties) key agreement protocols, which also are called conference key schemes, can be applied to distributed systems and wireless environments, such as ad hoc networks, for the purpose of multiparty secure communication. However, it is hard to extend two- or three-party schemes to multiparty ones with the guarantee of efficiency and security. In addition to the above two properties, interdomain environments should also be considered in key agreement systems due to diversified network domains. However, only few identity-based multiparty conference key agreement schemes for single domain environments and none for interdomain environments were proposed in the literature and they did not satisfy all of the security attributes such as forward secrecy and withstanding impersonation. In this paper, we will propose a novel efficient single domain identity-based multiparty conference key scheme and extend it to an interdomain one. Finally, we prove that the proposed schemes satisfy the required security attributes via formal methods.